Pervyse. L'église et le cimetière - The church and cemetry, GP060041 - Auteur inconnu (Wikimedia Commons)
Carte postale ancienne issue de Wikimedia Commons. Titre: Pervyse. L'église et le cimetière - The church and cemetry, GP060041. Title Pervyse. L'église et le cimetière - The church and cemetry Date [date de publication inconnue] Publisher Bruxelles: Marcovici Uniform title Pervijze (Nieuwpoort). Wereldoorlog I (1914-1918) Series Belgique. Province de Flandre occidentale. Cartes postales Belgium. Province of West-Flanders. Postcards België. Provincie West-Vlaanderen. Prentkaarten Genre Post cards Extent 1 kaart / postcard Graphic Brown Language French Additional info General note: Titelgegevens ontleend aan prentkaart Source Library Catalog Source ID lbsn9992541431701471
Licence Public domain via Wikimedia Commons
Keywords: carte postale; image; patrimoine; histoire locale; wikimedia commons; église